The Evaluation of Lesson Plans for History of English Literature - Widayanti, Maria Johana Ari (Language Circle: Journal of Language and Literature, 2019)
History of English Literature is one subject that is taught by semester fifth in English Literature students. This subject discusses about the history of English Language and Literature that includes the periods of literature and the characteristics. The aim of this research was to evaluate RPS in History of English Literature. The subjects were the fifth students of English Literature. The research used qualitative. In doing the research, I broke down all parts in lesson plan, such as capaian pembelajaran lulusan, capaian pembelajaran mata kuliah, deskripsi mata kuliah, and kemampuan yang diharapkan. After broke down all parts in lesson plan, I saw there was an importance thing in learning History of English Literature among fifth semester students of English Literature because this subject gave knowledge about the history of English, particularly the literature, the periods of literature, and the literary works in each period. Although the subject was important for students, there was imbalance between graduate learning outcome (Capaian Pembelajaran Lulusan) and course learning outcome (Capaian Pembelajaran Mata Kuliah). To solve its imbalance, I gave the knowledge about the development of language among students by lecturing and answering some questions. The result showed by giving questions about the development of language and the period of literature, students increased knowledge about this subject.